Additional local consolidative therapy has survival benefit over EGFR tyrosine kinase inhibitors alone in bone oligometastatic lung adenocarcinoma patients. (September 2019) - Hu, Fang; Li, Changhui; Xu, Jianlin; Guo, Jindong; Shen, Yinchen; Nie, Wei; Zheng, Xiaoxuan; Wang, Lixin; Zhang, Hai; Han, Baohui; Zhang, Xueyan
Highlights: The efficacy of LCT in bone oligometastatic lung adenocarcinoma is controversial. This study provided real-world treatment outcomes in bone oligometastatic patients. The current findings suggested that additional LCT could bring survival benefits. LCT plus EGFR-TKIs could be a better therapeutic option in these patients. Abstract: Objectives: Whether epidermal growth factor receptor tyrosine-kinase inhibitors (EGFR-TKIs) plus local consolidative therapy (LCT) has survival benefit over EGFR-TKIs alone in lung adenocarcinoma patients with EGFR mutation and bone oligometastases remains controversial. Materials and methods: We conducted a retrospective study to assess the effects of LCT in lung adenocarcinoma patients with bone oligometastases and EGFR mutation. The primary endpoint was overall survival (OS); the secondary endpoints was progression-free survival (PFS). Results: A total of 127 lung adenocarcinoma patients with EGFR mutation and bone oligometastases were assessed, including 65 patients received EGFR-TKIs alone (monotherapy group) and 62 patients received EGFR-TKIs plus local consolidative therapy (LCT) (combination group). Addition of LCT was associated with significantly longer OS (36.3 vs. 21.0 months, P = 0.01; hazard ratio [HR] = 0.537, 95% confidence interval [CI]: 0.360-0.801, p = 0.01) and PFS (14.0 vs. 8.1 months, P = 0.01; HR = 0.613, 95%CI: 0.427-0.879, p = 0.01) in the whole cohort. Conclusion: In lung adenocarcinoma patients with EGFR-mutation and bone oligometastases, LCT plus EGFR-TKIs therapy is associated with significantly longer OS and PFS compared with EGFR-TKIs therapy alone, indicating that LCT plus EGFR-TKIs therapy might be a better therapeutic option for this patient population.